Theoretical Exposition of Sufficiency Economy: Buddhist Ethics and the Spiritof Capitalism - Louangrath, Paul T. (วารสารวิชาการมหาวิทยาลัยอีสเทิร์นเอเชีย ฉบับวิทยาศาสตร์และเทคโนโลยี (Online), 2015)
See detail as file attached.